Ignacy Paderewski - Wapinski, Roman (Wroclaw : Warszawa : Zaklad Narodowy im. Ossolinskich, 1999)
The biography of the noted 20th century musician and diplomat, Ignacy Paderewski.
Includes bibliographical references (p. 212-[213]) and index.
Keywords: Paderewski, Ignace Jan, -- 1860-1941.; Statesmen -- Poland -- Biography; Musicians -- Poland -- Biography; Poland -- History -- 20th century